Moderating Role of Community Participation in the Relationship between Organizational Commitment, Good Corporate Governance, and Apparatus Performance - Setiyowati, Supami Wahyu; Indiraswari, Susmita Dian (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2025)
This study aims to analyze the influence of organizational commitment and Good Corporate Governance (GCG) on the performance of village officials, and to test the moderating role of community participation in the relationship. This study uses a quantitative approach with a survey method, involving 72 respondents consisting of officials and the community in Pakisaji District, Malang Regency. The data analysis technique uses Moderated Regression Analysis (MRA). The results of the study indicate that organizational commitment and the implementation of GCG principles have a significant effect on improving the performance of officials. Community participation also has a positive effect on the performance of officials, and significantly moderates the relationship between organizational commitment and official performance. However, community participation does not significantly moderate the relationship between GCG and official performance, indicating that the effectiveness of participation depends on the quality and structure of community involvement. These findings provide empirical contributions to the development of participatory and accountable village governance, as well as strengthening the role of internal and external factors in driving official performance.